2020
DOI: 10.1177/2325958219899305
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization among People Living with HIV/AIDS at the Kumba Health District, Cameroon

Abstract: We determined the level, type of stigma, and risk factors associated with stigmatization of people living with HIV/AIDS (PLWHA) by conducting a cross-sectional study from April to June 2018 in 3 HIV treatment centers in the Kumba Health District (KHD), Cameroon. We reviewed hospital registers, conducted focus group discussions, and administered structured questionnaires. For data analysis, we used the Statistical Package for Social Sciences version 20.0. We recorded a total stigma index score of 59.1. Internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…Different studies have indicated that a high proportion of PLWHA are being stigmatized and discriminated against by a significant proportion of the population they are sharing lives with even though the severities differ from country to country and from place to place [ 7 13 ]. The report from the 2017 Joint United Nations Program on HIV and AIDS (UNAIDS) showed that twenty percent of PLWHA across 19 countries where there were available data had avoided going to a clinic or hospital because of the fear of stigma or discrimination related to their HIV status [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have indicated that a high proportion of PLWHA are being stigmatized and discriminated against by a significant proportion of the population they are sharing lives with even though the severities differ from country to country and from place to place [ 7 13 ]. The report from the 2017 Joint United Nations Program on HIV and AIDS (UNAIDS) showed that twenty percent of PLWHA across 19 countries where there were available data had avoided going to a clinic or hospital because of the fear of stigma or discrimination related to their HIV status [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results from different studies have shown that Knowledge about HIV, educational status, age, place of residence, and marital status are some of the common factors associated with stigma and discrimination towards PLWHA [ 7 , 8 , 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main source of the negative attitudes to and irrational fears about HIV/AIDS dates back to the periods when little was known about the disease and its causes (Arrey et al, 2017; Deschepper, 2017; Horter et al, 2019). Studies performed with people from many different social classes have shown that people do not have adequate information about HIV/AIDS, which triggers social stigmatization (Bozkurt & Turan, 2020; Egbe et al, 2020; Tran et al, 2019). Most of the studies conducted in Turkey about HIV/AIDS have aimed to reveal the level of knowledge and attitudes of the society about HIV/AIDS and have shown that adolescents have inaccurate information about the routes of transmission of the disease; male students have increased awareness and information about AIDS; culture influences the attitudes towards the disease; and education is effective in improving the knowledge and attitudes about the disease (Bulduk et al, 2006; Cimen et al, 2013; Kaya et al, 2010; Saruç et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…HIV/AIDS‐related stigmatization has continued to cause anxiety in HIV‐positive individuals, their families, caregivers and even health care workers for a long time (Alexandra Marshall et al, 2017; Kabbash et al, 2018; Tran et al, 2019). Stigma is prevalent in rural and poverty‐stricken areas as a result of low education and lack of knowledge about HIV/AIDS (Bozkurt & Turan, 2020; Egbe et al, 2020). Stigmatization refers to excluding a person or a community from the rest of the society, discriminating against them, and seeing them as worthless.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation